Endurance training delays age of decline in leg strength and muscle morphology - Tarpenning, K. M.; Hamilton-Wessler, M.; Wiswell, R. A.; Hawkins, S. A. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: It has been reported that maximal strength peaks at approximately 30 yr of age, plateaus, and remains relatively stable for the next 20 yr, with an age-related decline in strength becoming significant after age 50. Much of the research attributes this decrease in peak force to age-associated reductions in muscle mass, with a selective atrophy and reduction in Type II fiber area and number being the primary factors. The influence that chronic endurance training has upon age-associated changes in muscular strength and muscle morphology has been largely undetermined. The purpose of this investigation was to examine the influence of chronic endurance training and age on leg extensor strength, and muscle fiber size and type distribution. METHODS: Male master runners (N = 107, age range = 40-88 yr) were tested for maximal strength of the leg extensor muscles. A subgroup of 30 master athletes participated in muscle biopsy testing. The effects of age were addressed by subdividing the sample into five cohorts. RESULTS: Peak isokinetic concentric torque did not differ between age groups until after age 70 yr. Regression analysis revealed a significant (P < 0.05, r(2) = 0.1838) age-associated decrease in relative strength (N.m.kg(-1) lean body mass). Type I and Type II fiber area and distribution did not differ between age groups through the eighth decade. CONCLUSIONS: These data suggest that chronic endurance training can delay the age of significant decline in peak torque and changes in muscle morphology characteristics of the vastus lateralis.